DAMPAK TEKNOLOGI INFORMASI, ETIKA PROFESI TERHADAP KINERJA AUDITOR - Zaleha, Putri Amelia; Novita, Novita (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2020)
This research ains to make analyze about impact to information technology and professional ethics of public accountants for auditor performance. The result expected to provide benefits in the audit process of financial statements that they can to improve the auditor performance in public accounting firms in DKI Jakarta area. Respondent used in this study are auditors who work in public accounting firms in DKI Jakarta area. Data collection methods used was questionnaire. The analytical method used in this research is descriptive analysis. The verification analysis is used to test the outer model, inner model and hypothesis testing with SmartPLS 3th version. Result of this research reveals that of the two variables; information technology and professional ethics of public accountants that have significant positive effect on auditor performance. The result of this analysis show from original sample value of information technology of 0.225 and professional ethics of 0.691. I t means that information technology and professional ethics have a significant effect on auditor performance. Meanwhile, the t-statistics value of information technology is 3.517 and professional ethics is 10.289. It means that information technology and professional ethics have a significant effect on auditor performance. The result illustrate that auditors feel benefits when implementing information technology consisting of artificial intelligence with use of being able to help analyze big data quickly, reduce errors. Then, cloud computing with the use of large storage scalability and can adapt to the needs and flexibility of data usage. Then there is professional ethics in supporting and improving the performance of auditors with the basic principles formulated by IAPI.